Integrasi Prinsip SDGs dalam Program Pemberdayaan Masyarakat Desa Berbasis Kearifan Lokal - Khasanah, Laila Nur; Setyo Prabowo, Bambang (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
The integration of Sustainable Development Goals (SDGs) principles into local wisdom-based village community empowerment programs is an important strategy for ensuring sustainable development at the local level. This study aims to analyze the integration patterns of SDGs principles into local wisdom-based village empowerment programs and assess their implications for the effectiveness of social, economic, and environmental development. This study uses a descriptive qualitative approach with a systematic literature review method for empirical research on village empowerment, community participation, collaborative governance, and the internalization of local values ​​within the SDGs agenda. The analysis results indicate that local wisdom acts as social capital that strengthens community participation, increases program legitimacy, and encourages the sustainability of SDGs implementation in villages. Effective integration is reflected in village development planning, community capacity building, local resource management, and economic development based on village potential. These findings confirm that a local wisdom-based approach is not only culturally relevant but also strategic in achieving village SDG targets in a contextual and measurable manner. This study provides conceptual and practical contributions to the development of village community empowerment policies that align with the principles of sustainable development.